Antifungal Activity of Bioactive Compounds Produced by the Endophytic Fungus Paecilomyces sp. (JN227071.1) against Rhizoctonia solani - Hawar, Sumaiya Naeema; Taha, Zainab K.; Hamied, Atyaf Saied; Al-Shmgani, Hanady S.; Sulaiman, Ghassan M.; Elsilk, Sobhy E. (International Journal of Biomaterials, 2023)
Biologically active natural compounds are molecules produced by plants or plant-related microbes, such as endophytes. Many of these metabolites have a wide range of antimicrobial activities and other pharmaceutical properties. This study aimed to evaluate (in vitro) the antifungal activities of the secondary metabolites obtained from Paecilomyces sp. against the pathogenic fungus Rhizoctonia solani. The endophytic fungus Paecilomyces was isolated from Moringa oleifera leaves and cultured on potato dextrose broth for the production of the fungal metabolites. The activity of Paecilomyces filtrate against the radial growth of Rhizoctonia solani was tested by mixing the filtrate with potato dextrose agar medium at concentrations of 15%, 30%, 45%, and 60%, for which the percentages of inhibition of the radial growth were 37.5, 50, 52.5, and 56.25%, respectively. The dual culture method was conducted on PDA medium to observe the antagonistic nature of the antibiotic impacts of Paecilomyces sp. towards the pathogenic fungus. The strength of the antagonistic impacts was manifested by a 76.25% inhibition rate, on a scale of 4 antagonistic levels. Ethyl acetate extract of Paecilomyces sp. was obtained by liquid-liquid partition of the broth containing the fungus. Gas chromatography-mass spectrometry (GC-MS) analysis identified the presence of important chemical components e.g., (E) 9, cis-13-Octadecenoic acid, methyl ester (48.607), 1-Heptacosanol, 1-Nonadecene, Cyclotetracosane (5.979), 1,2-Benzenedicarboxylic acid, butyl 2-methylpropyl ester, di-sec-butyl phthalate (3.829), 1-Nonadecene, n-Nonadecanol-1, Behenic alcohol (3.298), n-Heptadecanol-1, 1-hexadecanol, n-Pentadecanol (2.962), Dodecanoic acid (2.849), 2,3-Dihydroxypropyl ester, oleic acid, 9-Octadecenal, and (Z)-(2.730). These results suggest that secondary metabolites of the endophytic Paecilomyces possess antifungal properties and could potentially be utilized in various applications, such as environmental protection and medicine.